Hysteresis analysis of pre-pressed spring self-centering energy dissipation braces using different models. Issue 12 (September 2019) - Fan, Xiao-Wei; Xu, Long-He; Xie, Xing-Si; Sun, Yu-Sheng; Li, Zhong-Xian
The ability of an idealized piecewise-linear restoring force model and a nonlinear mechanical model to describe the hysteretic performances of the pre-pressed spring self-centering energy dissipation braces was evaluated based on experimental data. The hysteretic behaviors predicted by these two proposed models were compared with the experimental results of a typical prototype brace, and the results demonstrated that the two models can explain the brace force-time responses, and that the nonlinear mechanical model is more effective in describing the stiffness transition and energy dissipation of the brace. The two proposed models can be used for the design of the pre-pressed spring self-centering energy dissipation brace specimens, and the nonlinear mechanical model may be more useful for designing the structures with the pre-pressed spring self-centering energy dissipation braces. An orthogonal experiment was applied to analyze the influences of the key parameters on the performances of pre-pressed spring self-centering energy dissipation braces based on the nonlinear mechanical model. The results indicate that the friction slip force of energy dissipation mechanism, the pre-pressed force of self-centering mechanism, and the post-activation stiffness significantly affect the hysteretic performances and equivalent viscous damping ratios of the bracing system, while the changes in other parameters only produce slight effects. The determination of the pre-pressed force of the self-centering mechanism should be coordinated with the friction slip force of the energy dissipation mechanism to achieve a better hysteretic performance of the pre-pressed spring self-centering energy dissipation brace.